The impact of social media advertising characteristics on consumers' attitude towards advertising in China - Zhang, Jingjing (2022)
Traditional media advertising is gradually being replaced by new media advertising. Based on the development and changes of the internet, social media advertising is coming into the public eye and attracting attention. As a country with a large population, China is gradually gaining a position in the international market regarding commerce. With hundreds of millions of users, China has developed a distinctive social media culture. China has also developed several social media platforms with Chinese characteristics (e.g. Weibo, Tiktok, etc.), which are different from the typical social media in the international market. Therefore, this study is of great importance. Based on the research of previous theories, this dissertation proposes a conceptual model containing five advertising characteristics. The primary purpose is to explore the influence and role of different advertising characteristics on Chinese consumers' attitudes towards advertising on social media, and the main five factors selected are entertainment, informativeness, irritation, creativity and personalisation. The first three factors are based on previous research on the value of advertising. The last two factors are also derived from a few scholars' theoretical research on advertising characteristics. Moreover, the data for this study was collected on WenJuanXing (www.wjx.cn), a Chinese questionnaire distribution website, with 310 self-administered questionnaires, which were tested to remove 6 invalid data, ultimately leaving a valid sample of 306, with a data validity rate of approximately 98%. The study participants were aged between 18 and 34 years old and were those who were aware of or had been exposed to social media advertising in China. Most participants were university educated and currently hold full-time jobs. Regarding the methodology used in this study, it was a quantitative study. To be more specific, SPSS 27.0 was used during the study to conduct separate descriptive analyses, reliability tests, and multiple regression analyses on the data collected. The final results of this study showed that, with the exception of irritation, which did not affect Chinese consumers' attitudes towards social media advertising, the remaining four factors: entertainment, informativeness, creativity and personalisation were all found to have a positive effect on consumers' attitudes towards social media advertising. Therefore, this study makes a theoretical contribution. It increases our understanding of Chinese consumers' attitudes regarding social media advertising and verifies the extent to which selected characteristics of advertising on social media platforms influence consumer attitudes. The practical implications of the current findings are reflected in the study of a specific region, the Chinese market, and the inclusion in the study of two advertising characteristics that have rarely been studied in the social media arena: creativity and personalisation. Overall, This could provide a reference theory for Chinese advertising practitioners and international industries wishing to enter the Chinese market and new inspiration for their future work.